2018
DOI: 10.1186/s40168-018-0432-5
|View full text |Cite
|
Sign up to set email alerts
|

Trees, fungi and bacteria: tripartite metatranscriptomics of a root microbiome responding to soil contamination

Abstract: BackgroundOne method for rejuvenating land polluted with anthropogenic contaminants is through phytoremediation, the reclamation of land through the cultivation of specific crops. The capacity for phytoremediation crops, such as Salix spp., to tolerate and even flourish in contaminated soils relies on a highly complex and predominantly cryptic interacting community of microbial life.MethodsHere, Illumina HiSeq 2500 sequencing and de novo transcriptome assembly were used to observe gene expression in washed Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 223 publications
(244 reference statements)
9
66
0
5
Order By: Relevance
“…Default recommended annotation uses four sequence repositories with strict BLASTn criteria (>99% identity and coverage) providing each amplicon with up to four pools of labels from: NCBI‐curated bacterial and Archaea RefSeq, NCBI nr/nt, SILVA and Ribosomal Database Project (RDP). Annotation selection against the four databases is based on de novo metatranscriptomics strategy (Brereton et al ., ; Gonzalez et al ., ), where all potential annotation is retained to allow for informed annotation selection and downstream interpretation. BLASTn returns with a query identity and coverage <99% are discarded and the highest identity/coverage scores are selected per query.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Default recommended annotation uses four sequence repositories with strict BLASTn criteria (>99% identity and coverage) providing each amplicon with up to four pools of labels from: NCBI‐curated bacterial and Archaea RefSeq, NCBI nr/nt, SILVA and Ribosomal Database Project (RDP). Annotation selection against the four databases is based on de novo metatranscriptomics strategy (Brereton et al ., ; Gonzalez et al ., ), where all potential annotation is retained to allow for informed annotation selection and downstream interpretation. BLASTn returns with a query identity and coverage <99% are discarded and the highest identity/coverage scores are selected per query.…”
Section: Methodsmentioning
confidence: 99%
“…BLASTn returns with a query identity and coverage <99% are discarded and the highest identity/coverage scores are selected per query. When the highest identity/coverage for a given high‐count sequence is shared amongst different blast returns from a database, all are retained as equally ‘good’ annotation and designated as ambiguous hits (borrowed from the idea of secondary annotation in metatranscriptomics [Brereton et al ., ; Gonzalez et al ., )]. Accurately reporting ambiguity is important as fragments of a specific 16S rRNA gene [or a gene's entire sequence (Vetrovsky and Baldrian, )] are sometimes 100% similar between known species; the relative utility of a specific amplicon as a barcode therefore varies based on the species present in a sample as well as the technology used for sequencing and data processing.…”
Section: Methodsmentioning
confidence: 99%
“…These mechanisms are thought to enable holobionts to adapt within a single or a few generations (Voss et al, 2015;Rosenberg and Zilber-Rosenberg, 2016). It has recently been shown that the response of willows to stressful conditions (soil contamination) results in large shifts in the metatranscriptome of root and rhizosphere bacterial and fungal communities, but not in the plant root transcriptome (Gonzalez et al, 2018;Yergeau et al, 2018). Taken together, these results emphasize the importance of the plant microbiota in the response to environmental stresses and confirms that microbiota manipulation is a viable alternative to optimize phytoremediation (El Amrani et al, 2015;Quiza et al, 2015).…”
Section: Microbes As Hydrocarbon Degradersmentioning
confidence: 65%
“…The rhizosphere microbes, especially bacteria, are thought to be the major players in organic contaminant degradation during rhizoremediation (Bell et al, 2014a,b;El Amrani et al, 2015), and recent plant-microbe metatranscriptomic studies confirmed that the hydrocarbon degradation genes expressed in the root-rhizosphere environment were mostly linked to bacteria (Gonzalez et al, 2018;Yergeau et al, 2018) (Box 1). Petroleum hydrocarbon contamination is often composed of a mixture of saturated aliphatic (alkanes) and aromatic hydrocarbons (including polycyclic aromatic hydrocarbons, PAHs).…”
Section: (A) (B)mentioning
confidence: 99%
“…Transcripts with E values < 1e‐6 were kept. The E ‐value cut‐off was selected based on previous studies (Hesse et al ., ; Quandt et al ., ; Comtet‐Marre et al ., ; Meiser et al ., ; Gonzalez et al ., ) and after manual examination of a subset of sequences and their BLASTX results. To gain more taxonomic information and to confirm that the selected transcripts really belong to fungi, transcripts were first translated into proteins with Transdecoder (Haas et al ., ) and an additional round of BLASTP against the NCBI Non‐Redundant (NR) protein database was performed, saving the top five hits.…”
Section: Methodsmentioning
confidence: 99%